Los símbolos literarios Autores - Garcia Peña, Lilia Leticia (Universidad de Colima, 2026)
Approaching symbols in literary works will always be an exciting journey. Through them, we may see the world that surrounds us with new eyes. We may read dreams, words, and books, discovering wonderful senses. The universe of symbols will always be an invitation to the knowledge of infinite human realities. Recognizing and reading literary symbols expands our experience by way of the joyous reading of literary texts.